Approaches to the removal of T-lymphocytes to minimize graft-versus-host disease in patients with primary immunodeficiencies who do not have a matched sibling donor. Issue 6 (December 2017) - Slatter, Mary A.; Gennery, Andrew R.
Abstract : Purpose of review: Since the advent of T-lymphocyte depletion in hematopoietic stem cell transplantation (HSCT) for primary immunodeficiency, survival following this procedure has remained poor compared to results when using matched sibling or matched unrelated donors, over the last 40 years. However, three new techniques are radically altering the approach to HSCT for those with no matched donor, particularly those with primary immunodeficiencies which are not severe combined immunodeficiency. Recent findings: Three main techniques of T-lymphocyte depletion are altering donor choice for patients with primary immunodeficiencies and have improved transplant survival for primary immunodeficiencies to over 90%, equivalent to that for matched sibling and matched unrelated donor transplants. CD3 + T cell receptor (TCR)αβ + CD19 + depletion, CD45RA depletion and use of posttransplant cyclophosphamide give similar overall survival of 90%, although viral reactivation remains a concern. Further modification of CD3 + TCRαβ + CD19 + depletion by adding back inducible caspase-9 suicide gene-modified CD3 + TCRαβ + T-lymphocytes may further improve outcomes for patients with systemic viral infection. Summary: Over the last 5 years, the outcomes of HSCT using new T-lymphocyte depletion methods have improved to the extent that they are equivalent to outcomes of matched sibling donors and may be preferred in the absence of a fully matched sibling donor, over an unrelated donor to reduce the risk of graft versus host disease.